Care and Support for Adolescents Living with HIV/AIDS in School Settings: Perspectives of Teachers and Administrators in the Southern Highlands of Tanzania - Andrew Kigombola; John George; Mastidia Rutaihwa; Beauty Mwambebule; Neema Mlole; Edgar Lungu (Shiraz University of Medical Sciences, 2024)
Background: Adolescents living with HIV (ALHIV) encounter diverse challenges in school settings that impact their well-being and academic performance. This study sought to delve into the viewpoints of teachers and administrators regarding the care and support accessible to ALHIV in schools.Methods: In 2021, a qualitative study was conducted employing focused group discussions (FGDs) and key informant interviews (KIIs). The study was conducted in the Njombe and Songwe regions, encompassing four districts and eight schools. FGDs were held with schoolteachers and matrons/patrons, while KIIs were conducted with coordinators at the regional and district levels. Thematic analysis was employed for data analysis.Results: Various forms of support for ALHIV in schools were identified. Schools had designated health teachers/matrons/ patrons responsible for addressing health-related issues, including those affecting ALHIV. Assistance for clinic visits and medication adherence was readily available. Peer clubs were established to combat stigma and discrimination while providing additional support. Nevertheless, challenges such as staff members' limited knowledge and skills, reluctance to disclose, inadequate nutritional support, and insufficient backing from regional and district administrators persist.Conclusion: The study underscored the existence of care and support mechanisms for ALHIV in school settings while pinpointing areas for enhancement. Recommendations encompass capacity building for teachers and staff, bolstering support for disclosure, offering nutritious dietary options, reinforcing peer clubs, and fostering collaboration between the education and health sectors. These findings can inform the development of comprehensive interventions to support ALHIV in school settings better, ultimately advancing their well-being and academic achievements.